INFLUENCE AND PROMOTION ON PURCHASE DECISIONS FOR MR DIY PRODUCTS IN PALEMBANG CITY - Falatehan, Falatehan; Mario, Mario; Yohanes, Jonathan; Samatha, Felisca; Tampubolon, Naomi Oktavia (Jurnal Manajemen, 2025)
This research aims to determine the significant influence of promotions and impulse buying on the purchasing decisions of MR.DIY Indonesia products. This study uses primary data. The population in this research consists of customers or consumers of MR.DIY Indonesia, with a sample size of 120 respondents.The sampling technique employs Slovin’s formula. The analytical techniques used in this study include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, T-tests, F-tests,and the coefficient of determination, using SPSS software. The results show that there is a significantinfluence of promotions and impulse buying on the purchasing decisions of MR.DIY Indonesia products.